Surgical Site Infection with and without Prophylatic Antibiotic in Children undergoing Elecltive Inguinal Herniotomy - Nabi Bux Napar, Noor Ahmed Shaikh, Imamuddin Baloch, Azhar Ali Shah, Bushra Shaikh, Ishrat Mahtam (Journal of Rawalpindi Medical College, 2021)
Objective: This study was aimed at determining the frequency of surgical site infection in children undergoing elective inguinal herniotomy with and without prophylactic antibiotic. Study design: Prospective comparative study. Settings: Pediatric surgery Department, Ghulam Muhammad Mahar Medical College Sukkur. Study duration: From 1st February 2020 to 31th March 2021. Methodology: One hundred and sixty patients selected for this study and were equally divided into two groups. Group A received antibiotic prophylaxis (Injection ceftriaxone 50mg/kg) before the induction of general anesthesia, whereas Group P received placebo before the induction of general anesthesia. Demographic data and duration of surgery was noted on a proforma. Surgical procedure was carried out following standard surgical protocols. Post-operatively all patients were observed by an independent observer. Patients were observed for post-operative fever, inflammation of the surgical site and discharge from the site of incision. Wound was examined on 1st, 3rd, 7th and 30th post-operative day. For labeling Surgical Site Infection, Center of Disease criteria was followed. Results: Demographic data of both groups was comparable. Mean duration of surgery in group A was 29.61±7.47 minutes, while it was 32.97±8.73 minutes in group P with p-value of 0.08. Out of 160 patients, thirteen patients developed surgical site infection; 5 (6.25%) patients belonged to group A, while 8 (10%) belonged to group P with a p-value of 0.385. Conclusion: It is concluded in our study that use of prophylactic antibiotics in elective herniotomy cases performed in pediatric patients do not significantly decrease the incidence of Surgical Site Infection.